Controlled post-polymerization modification through modulation of repeating unit reactivity: Proof of concept discussed using linear polyethylenimine example. (5th March 2021) - Kopiasz, Rafał J.; Kozon, Dominika; Pachla, Julita; Skórka, Łukasz; Jańczewski, Dominik
Abstract: Post-polymerization modification (PPM) is a frequently used approach to alter polymer properties which cannot be achieved through direct polymerization of functional monomers. While well-defined polymeric materials can be obtained when the PPM is performed in an exhaustive manner, some applications require a partial polymer modification. The partial PPM approach typically uses kinetic or reactant ratio control and does not yield well-defined polymeric products. A proof-of-concept for a controlled PPM method, which is possible thanks to reactivity modulation of polymer repeating units (r.u.), is presented. The alkylation of fully N -methylated linear polyethylenimine (Me-L-PEI) is used as an example for the method and provides support for the controlled character of the process. Reactivity modulation, along the polymeric chain, is achieved thanks to the strong influence of already modified Me-L-PEI r.u. (quaternary ammonium salts) on the electron properties and reactivity of neighboring non-modified r.u. Experimental results, supported by numerical simulation and DFT calculations, provide a basis for a novel approach for obtaining well-defined polymeric structures. Graphical abstract: Image 1 Highlights: Controlled post-polymerization modification method leading to well-defined product Reactivity modulation of polymer repeating units The influence of field effect on PEI alkylation process Numerical simulation of controlled post-polymerization modification